Staphylococcal Complement Evasion Protein Sbi Stabilises C3d Dimers by Inducing an N-Terminal Helix Swap - Dunphy, Rhys W.; Wahid, Ayla A.; Back, Catherine R.; Martin, Rebecca L.; Watts, Andrew G.; Dodson, Charlotte A.; Crennell, Susan J.; van den Elsen, Jean M. H. (Frontiers in Immunology, 2022)
Staphylococcus aureus is an opportunistic pathogen that is able to thwart an effective host immune response by producing a range of immune evasion molecules, including S. aureus binder of IgG (Sbi) which interacts directly with the central complement component C3, its fragments and associated regulators. Recently we reported the first structure of a disulfide-linked human C3d17C dimer and highlighted its potential role in modulating B-cell activation. Here we present an X-ray crystal structure of a disulfide-linked human C3d17C dimer, which undergoes a structurally stabilising N-terminal 3D domain swap when in complex with Sbi. These structural studies, in combination with circular dichroism and fluorescence spectroscopic analyses, reveal the mechanism underpinning this unique helix swap event and could explain the origins of a previously discovered N-terminally truncated C3dg dimer isolated from rat serum. Overall, our study unveils a novel staphylococcal complement evasion mechanism which enables the pathogen to harness the ability of dimeric C3d to modulate B-cell activation.